PENDIDIKAN DAN PELATIHAN PEDULI LINGKUNGAN PADA MASYARAKAT PANTAI MANGROVE DI KAMPUNG NIPAH, KABUPATEN SERDANG BEDAGAI - Rahmat Hidayat; Zamakhsyari bin Hasballah Thaib; Mukhamad Hadi Musolin; Amiruddin Ahmad Malindo (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Environmental education and training are important ways to raise awareness and make coastal communities more active in protecting mangrove ecosystems. This project aims to explain how the implementation and impact of environmental education and training programs affect communities in the Mangrove Coast area, Kampung Nipah, Serdang Bedagai Regency. The methods used were community outreach, mangrove area management, and engagement with parties involved in training activities. These activities show that environmental education and training have a positive impact on increasing community knowledge, attitudes, and actions in preserving the sustainability of mangrove forests. The community now better understands the ecological and economic benefits of mangroves and has begun to actively participate in efforts to manage the area sustainably. The implementation of the activity encountered some obstacles due to inadequate facilities and infrastructure. Therefore, continuous support from the government and relevant parties is needed so that environmental awareness education and training programs can run well and have a sustainable impact on the preservation of the mangrove forest ecosystem and the welfare of communities living in coastal areas.